2020
DOI: 10.1111/are.14514
|View full text |Cite
|
Sign up to set email alerts
|

Attractability and palatability of liquid protein hydrolysates for Nile tilapia juveniles

Abstract: The experiment was conducted with the aim of determining the attractability and palatability of liquid protein hydrolysates for Nile tilapia. Five experimental diets were formulated containing 5% inclusion of fishmeal (FPE; positive control), 5% inclusion of liquid protein hydrolysate of porcine mucosa (PHM), 5% inclusion of liquid protein hydrolysate of poultry (PHF), 5% inclusion of liquid fish oil (OPE) and a diet without fishmeal (negative control). Five juveniles (2.51 ± 0.13 g) were distributed in 10 L t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Likewise, some other amino acids were evaluated as repulsive, such as tryptophan, arginine, threonine, methionine, phenylalanine, serine and valine (Alves, Oliveira, Luczinski, et al, 2020;Alves, Oliveira, Sosa, et al, 2020;Alves, Silva, et al, 2019;Hara, 2006Hara, , 2011Kasumyan, 1997;Kasumyan & Doving, 2003;Kasumyan & Morsi, 1996;Kasumyan & Sidorov, 2012;Lokkeborg et al, 2014;Siikavuopio et al, 2017;Suresh et al, 2011). In an amino acid profile analysis performed on the hydrolysed ingredients tested, we observed that the porcine liver hydrolysate has a higher concentration of asparagine compared with the other hydrolysed ingredients (Table 4).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Likewise, some other amino acids were evaluated as repulsive, such as tryptophan, arginine, threonine, methionine, phenylalanine, serine and valine (Alves, Oliveira, Luczinski, et al, 2020;Alves, Oliveira, Sosa, et al, 2020;Alves, Silva, et al, 2019;Hara, 2006Hara, , 2011Kasumyan, 1997;Kasumyan & Doving, 2003;Kasumyan & Morsi, 1996;Kasumyan & Sidorov, 2012;Lokkeborg et al, 2014;Siikavuopio et al, 2017;Suresh et al, 2011). In an amino acid profile analysis performed on the hydrolysed ingredients tested, we observed that the porcine liver hydrolysate has a higher concentration of asparagine compared with the other hydrolysed ingredients (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that each fish species is attracted to different combinations of amino acids and not all amino acids are palatable to all species (Hara, 2011; Moraes, 2016; Yacoob & Browman, 2007). There is evidence of differences between species regarding the types of amino acids that act as food stimulants or repellents, which can influence the animal's final decision (Alves, Oliveira, Luczinski, et al, 2020; Moraes, 2016; Olsen & Lundh, 2016); thus, important stimulants differ even among closely related species (Kasumyan & Doving, 2003). Kasumyan (1997) investigated 21 different fish species and the data revealed that the number of free amino acids that acted as food stimulants ranged from 0 to 13 and that in just a few fish species the number of stimulant amino acids varies by more than ten.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations